2019
DOI: 10.1097/meg.0000000000001316
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up after cure from chronic hepatitis C virus infection shows occult hepatitis and a risk of hepatocellular carcinoma in noncirrhotic patients

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
4
8
0
4
Order By: Relevance
“…Occult HCV infection is defined by the presence of HCV RNA in liver tissue or peripheral blood mononuclear cells (PBMCs) of patients who test negative for serum HCV RNA, with or without the presence of anti‐HCV antibodies . A few groups reported the presence of occult HCV infection in patients with liver test abnormalities without detectable serum anti‐HCV antibodies and HCV RNA, as well as in patients with spontaneous or treatment‐induced clearance of HCV . Conversely, as we have previously reported, there is a lack of evidence of occult HCV infection after kidney transplantation in patients who had spontaneous HCV clearance or after interferon therapy before transplantation while on dialysis .…”
Section: Introductionmentioning
confidence: 73%
“…Occult HCV infection is defined by the presence of HCV RNA in liver tissue or peripheral blood mononuclear cells (PBMCs) of patients who test negative for serum HCV RNA, with or without the presence of anti‐HCV antibodies . A few groups reported the presence of occult HCV infection in patients with liver test abnormalities without detectable serum anti‐HCV antibodies and HCV RNA, as well as in patients with spontaneous or treatment‐induced clearance of HCV . Conversely, as we have previously reported, there is a lack of evidence of occult HCV infection after kidney transplantation in patients who had spontaneous HCV clearance or after interferon therapy before transplantation while on dialysis .…”
Section: Introductionmentioning
confidence: 73%
“…Chronic HCV is a major cause of liver fibrosis leading to cirrhosis and hepatocellular carcinoma [23,24]. The rate of progression of fibrosis is highly variable, where progression to cirrhosis ranges from 10 to 30 years [25,26]. The prevalence of chronic HCV infection in Egypt is 14.8% [2], underscoring importance to highlight various parameters associated with fibrosis severity in chronic HCV Egyptian patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the HCC subgroup had a mean AFP value of 313 ± 132 μg/dL and FIB‐4 value 4.2 ± 0.7. Another recent study revealed that an increased risk of HCC could persist in the long term after SVR, even in non‐cirrhotic patients …”
Section: Discussionmentioning
confidence: 99%